Effect of Giving Urban Waste Compost as a Growing Media to the Pb Content of Soil and Mustard - Fachrul Rozy Ariandy; Sarifuddin Sarifuddin; Posma Marbun (Jurnal Agroekoteknologi, 2018)
The research was aimed to know that accumulation of lead in soil and mustard due to urban waste compost application. The researh was held in gauze house and analyzed in Balai Pengkajian Teknologi Pertanian (BPTP) Laboratory, North Sumatera in April -July 2016. The research used randomized block design factorial with two treatment factors those are the depth of layers of urban waste compost with 3 level of treatment ; S1 (upper layer), S2 (middle layer), S3 (bottom layer) and growing media composition with 5 level of treatment ; M0 (100% soil), M1 (25% compots + 75% soil), M2 (50% compost and 50% soil), M3 (75% compost + 25% soil), M4 (100% compost) with 3 replications. The result showed that giving25% urban waste compost can increase of production of mustard, soil pH, soil C-organic, total Pbsoil and Pb in plants and it’s value exceeds the threshold. The depth of layers of urban waste compost significant effect on total Pb soil and Pb in plants and it’s value exceeds the threshold. Interaction amount of compost and the depth of layers of urban waste compost were not significant increased of production of mustard, but significant increased of soil pH, soil C-organic, total Pbsoil and Pb in plants. Keyword :Mustard, Pb, Urban Waste Compost